Exploring Learning Strategies on English Speaking Skill for Visually Impaired Students at SMPLB A YPAB Surabaya - Hikmah, Nurul (RETAIN, 2021)
This article describes the results on examining learning strategies applied by visually impaired students in learning English speaking skills including the strength and weaknesses of using it. This study involved 10 students of 8th and 9th graders SMPLB A YPAB Surabaya, using a qualitative descriptive research design. The data collection included student interviews and field observations. The results revealed that students applied several learning strategies include memorizing when they prefer to remember rather than note; cognitive such as practice, repeating, translating; social strategies as indicated by asking their teacher or others, ask for reviews, additional explanations, and confirming; compensation, by overcoming speaking limitation, trying to provide answers, and using language mixing. This also equipped with assistive technology utilization during learning such as using screen reader on their smart phone. Those assist their learning activities more effective and efficient. The implementation of those strategies influenced by the learner autonomy which determines the frequency of using selected strategies and the achievement of applying it. Therefore, they can overcome the differences in learning methods they received from the English teacher at school. Thus, visually impaired students have own learning strategies that they can apply according to their ability to understand English especially for speaking skills.